2014
DOI: 10.1002/mgg3.75
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency of insulin gene enhancer protein 1 (ISL1) is associated with d‐transposition of the great arteries

Abstract: Congenital heart defects are the most common malformation, and are the foremost causes of mortality in the first year of life. Among congenital heart defects, conotruncal defects represent about 20% and are severe malformations with significant morbidity. Insulin gene enhancer protein 1 (ISL1) has been considered a candidate gene for conotruncal heart defects based on its embryonic expression pattern and heart defects induced in Isl1 knockout mice. Nevertheless no mutation of ISL1 has been reported from any hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…S1a–d), 23 which survives until birth, allowing us to analyze the role of Isl1 in SHF structures that are dependent on Isl1, as well as during later stages of embryonic heart development. Consistent with human studies which identified ISL1 variations and deletions contributing to congenital heart disease, 16,17 all Isl1 hypomorphic mice ( Isl1 -f;neo/f;neo) died shortly after birth with severe cardiac malformations. Wholemount and histological analyses of Isl1 hypomorphic embryos at E12.5 (Fig.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…S1a–d), 23 which survives until birth, allowing us to analyze the role of Isl1 in SHF structures that are dependent on Isl1, as well as during later stages of embryonic heart development. Consistent with human studies which identified ISL1 variations and deletions contributing to congenital heart disease, 16,17 all Isl1 hypomorphic mice ( Isl1 -f;neo/f;neo) died shortly after birth with severe cardiac malformations. Wholemount and histological analyses of Isl1 hypomorphic embryos at E12.5 (Fig.…”
Section: Resultssupporting
confidence: 82%
“…Similarly, genetic variations in ISL1 have been associated with susceptibility to ventricular septal defect 43 and non-syndromic, complex congenital heart disease 17 in human patients, whereas ISL1 haploinsufficiency is associated with d-transposition of the great arteries. 16 Thus, our Isl1 hypomorphic mouse model represents a valuable genetic system to gain new insights into the etiology of congenital heart defects and for developing novel therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to what occurs in Nkx2.5, mutations in the human Isl1 gene are associated with a diverse range of cardiac malformations (43)(44)(45). Therefore, it is not surprising that a complex netdistinction probably lies in the requirement of physiological hypoxia for embryonic heart development, while hypoxia is an unfavorable condition in most adult organs.…”
Section: Discussionmentioning
confidence: 97%
“…Dye-labeled DNA sequencing technique is still an important tool for clinical decision making on cancer [3] , [4] , [5] , drug metabolism genotyping [6] , [7] , [8] , pathogen identification [9] , [10] , [11] , inherited disease [12] , [13] , [14] , [15] , [16] , [17] and so on [18] , [19] . However, the methods remain laborious and time-consuming.…”
Section: Datamentioning
confidence: 99%